Effect of Sudden Deprivation of Sensory Inputs From Periodontium on Mastication - Grigoriadis, Anastasios; Kumar, Abhishek; Åberg, Magnus K.; Trulsson, Mats (Frontiers in Neuroscience, 2019)
Objective: To investigate the effect of sudden deprivation of sensory inputs from the periodontium on jaw kinematics and time-varying activation profile of the masseter muscle. Methods: Fourteen (age range: 22-26 years; four men) healthy and natural dentate volunteers participated in a single experimental session. During the experiment, the participants were asked eat six hard visco-elastic test food models, three each before and after an anesthetic intervention. The movements of the jaw in three dimensions and electromyographic (EMG) activity of the masseter muscle on the chewing side were recorded. Results: The results of the study showed no significant differences in the number of chewing cycles (P=0.233) and the duration of chewing sequence (P=0.198) due to sudden deprivation of sensory inputs from the periodontium. However, there was a significant increase in the jaw opening velocity (P=0.030) and a significant increase in the duration of occlusal phase (P=0.004) during the anesthetized condition. The EMG activity of the jaw closing phase was significantly higher during the control condition (116.5 arbitrary units (AU)) than anesthetized condition (93.9 AU). The temporal profile of the masseter muscle showed a biphasic increase in the excitatory muscle drive in the control condition but this increase was virtually absent during the anesthetized condition. Conclusion: Sudden deprivation of sensory inputs from the periodontium affects the jaw kinematics and jaw muscle activity, with a clear difference in the time-varying activation profile of the masseter muscle. The activation profile of the masseter muscle show that periodontal mechanoreceptors contribute to approximately twenty percent of the EMG activity during the jaw closing phase.